Effects of Sucrose, Trehalose, and Fructose on Whole Ovarian Cryopreservation in a Rat Model - Lingyun Xie; Yan Ding; Ping Xu; Keqin Hua; Xuyin Zhang (IMR Press, 2024)
Background: Recently, the utilization of sugar as a cryoprotectant has garnered significant attention. Sucrose and trehalose, as non-permeable cryoprotectants, can effectively regulate the osmotic pressure inside and outside cells while maintaining cell membrane stability during cryopreservation. Furthermore, it has been observed that monosaccharides sugars, particularly fructose, exhibit superior efficacy in preserving the quality of frozen substances as compared to disaccharides and trisaccharides sugars. Nevertheless, there is currently limited research assessing the cryopreservation effects of sucrose, trehalose, and fructose. The objective of this experiment is to identify the best cryoprotectant between sucrose, trehalose, and fructose for intact rat ovaries. Methods: Intact ovaries with blood vessels were obtained from 20 adult Lewis female rats and divided accordingly into four groups: control (non-vitrified), sucrose, fructose, and trehalose. The ovarian samples were subjected to a stepped cryoprotectant exposure and subsequently follicular histological analysis using light and electron microscopy. Ovarian cell apoptosis was evaluated by BCL2-Associated X (BAX) immunohistochemistry and Terminal Deoxynucleotidyl Transferase-Mediated Deoxyuridine Triphosphate nick End-Labeling (TUNEL) analyses. Results: The sucrose and the trehalose groups preserved the ovarian histological structure better than the fructose group. Additionally, there was no statistical difference in the total follicle number between the sucrose and trehalose groups, but the percentage of apoptotic cells in the trehalose group was significantly lower than that of the sucrose group (p < 0.01). Conclusions: Sucrose and trehalose perfusion protocols preserved the ovarian histology. However, the least apoptotic changes were observed in the trehalose group. The study suggested that trehalose would be a well-applied cryoprotectant in the cryopreservation of intact rat ovaries.